Pengembangan Modul Pembelajaran Anak Berkebutuhan Khusus Implementasi Kurikulum Merdeka di SD Negeri Inklusi - Purnama Pertiwi, Ratih; Sri Enggar Kencana Dewi (Jurnal Elementaria Edukasia, 2023)
This research aims to create a learning module that can support children with special needs in following the merdeka curriculum in Inclusive elementary Schools. The merdeka curriculum is an approach to learning that encourages flexibility in its process, making specifik adjustments for children with special needs essential. This research adopts the Research and Development method based on the ADDIE theory by Dick and Carey, Which consists of five stages: Analysis, Desaign, Development, Implementation, and Evaluation. This research only reached the third stage, which is the development stage, because the research was conducted using a predetermined Likert scale questionnaire instrument. the results of the questionnaire indicate that students are highly interested in this learning module. Furthermore, the validation of the materials and learning media also indicates that this module is highly suitable and effective for use in teaching children with special needs. Therefore, this learning module is considered both attractive and effective for use. İt is hoped that this research can be continued by adding more content to the learning module and implementing it in futher teaching processes